CHARMY an extensible tool for architectural analysis. - Inverardi, Paola
CHARMY is a framework for designing and validating architectural specifications. In the early stages of the software development process, the CHARMY framework assists the software architect in the design and validation phases. To increase its usability in an industrial context, the tool allows the use of UML-like notations to graphically design the system. Once the design is done, a formal prototype is automatically created for simulation and analysis purposes. The framework provides extensibility mechanisms to enable the introduction of new design and analysis features.
Keywords: Software; Software engineering; Software architectures; Computing methodologies; Simulation and modeling; Model validation and analysis; Design; Verification; Model checking; Software architectures